Professional support staff at higher education institutions in Sweden: roles and success factors for the job. Issue 4 (2nd October 2017) - Ryttberg, Malin; Geschwind, Lars
Abstract : This paper aims to analyse and discuss the professional support staff at higher education institutions in Sweden in terms of how they view their roles and what the success factors for them are. The study is based on semi-structured interviews with support staff from the fields of business liaison, internationalisation and strategic research support. The results show that the participants have shaped their own roles and see themselves as back-office staff. This can make it challenging for them to prove their contribution to the academic activities of education and research. Because they neither identify themselves as administrators nor hold academic positions, their ability to build credibility on a personal basis is a central success factor. Aware of being actors in a culture dominated by academic values and norms, they see a more transparent discussion of their roles as a desirable development in the sector.